Adenocarcinoma of retinal pigment epithelium. Issue 7 (July 1987) - Ramahefasolo, S; Soubrane, G; Dhermy, P; Godel, V; Regenbogen, L; Coscas, G
Abstract : This report describes a 41-year-old man with an intraocular tumour misinterpreted clinically as choroidal melanoma. The fluorescein angiographic features were not fully characteristic of uveal malignancy, and indeed histopathology revealed the diagnosis of adenocarcinoma of the retinal pigment epithelium. It is suggested that, in cases with the fundus and angiographic findings described here, the rare possibility of adenocarcinoma of retinal pigment epithelium should be kept in mind. Of particular interest were the changing pathological findings in the various parts of the tumour, which paralleled the fluorescein angiographic pattern.